A comprehensive environmental index for monitoring ecological quality of typical alpine wetlands in Central Asia - Jiudan Zhang; Junli Li; Changming Zhu; Anming Bao; Amaury Frankl; Philippe De Maeyer; Tim Van de Voorde (Ecological Indicators)
Understanding the long-term ecological quality trends of alpine wetlands in cold mountainous areas of Central Asia is essential for effective conservation and restoration efforts. However, inconsistencies and ambiguities regarding wetland health persist due to methodological variations and differences in spatio-temporal scale among studies. This study employed a deep-learning semantic segmentation model to map the structural changes of the Bayanbulak alpine wetland using Landsat imagery from 1977 to 2022. Subsequently, an Alpine Wetland Ecological Quality Index (AWEQI) was developed to quantify the changes in ecological quality over this period. Furthermore, the driving factors behind these changes were analyzed by combining meteorological precipitation data with human activities. Long-term monitoring results indicate that the Bayanbulak Wetland has experienced significant expansion, with its ecological quality improving remarkably over the past 45 years, particularly in the Big Urdus basin. The wetland area expanded from 969.11 km2 to 1,108.75 km2 at an average of 1.83 km2 per year. Meanwhile, improvements were also observed in hydrological conditions, vegetation vitality, and aboveground biomass, coupled with a reduction in wetland landscape fragmentation, improving ecological stability. Moreover, variations in water network density across basins influenced the effectiveness of restoration, underscoring the spatial heterogeneity of ecological recovery. Increased precipitation and improved conservation measures have contributed to these positive trends. This study offers a scientific foundation for adaptive strategies to sustain the resilience of alpine wetland ecosystems.